Analisis Pengaruh Belanja Pemerintah Bidang Kesehatan dan Infrastruktur terhadap Indeks Pembangunan Manusia (IPM) di Provinsi Sumatera Utara - Sarah E Simamora; Puti Andiny; Yani Rizal; Safuridar Safuridar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the impact of government spending in the health and infrastructure sectors on the Human Development Index (HDI) in North Sumatra Province over the period 2014-2023. The independent variables in this study are health and infrastructure spending, while the dependent variable is HDI. Secondary data were obtained from the Central Bureau of Statistics (BPS) and the Directorate General of Fiscal Balance (DJPK). The analysis method used is multiple linear regression with the assistance of Eviews 10 software. The results indicate that health spending has a positive and significant effect on HDI, whereas infrastructure spending has a negative and insignificant effect on HDI. The F-test confirms that health and infrastructure spending simultaneously have a significant effect on HDI. The coefficient of determination (Adjusted R-squared) shows that the independent variables explain 80.63% of the variation in HDI. These findings highlight the importance of increasing and stabilizing budget allocation in the health sector to strengthen (HDI )in North Sumatra. This study suggests a need for budget consistency in the infrastructure sector to ensure its long-term impact on HDI.